2018
DOI: 10.1186/s12970-018-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a brief general and sports nutrition knowledge questionnaire and assessment of athletes’ nutrition knowledge

Abstract: BackgroundThe Nutrition for Sport Knowledge Questionnaire (NSKQ) is an 89-item, valid and reliable measure of sports nutrition knowledge (SNK). It takes 25 min to complete and has been subject to low completion and response rates. The aim of this study was to develop an abridged version of the NSKQ (A-NSKQ) and compare response rates, completion rates and NK scores of the NSKQ and A-NSKQ.MethodsRasch analysis was used for the questionnaire validation. The sample (n = 181) was the same sample that was used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 33 publications
6
89
2
Order By: Relevance
“…Some supplements may have little or no effect on performance, health, and restitutions while others may cause damage in too large amounts. An educational test and teaching program developed to investigate and educate athletes in sports nutrition has been suggested …”
Section: Discussionmentioning
confidence: 99%
“…Some supplements may have little or no effect on performance, health, and restitutions while others may cause damage in too large amounts. An educational test and teaching program developed to investigate and educate athletes in sports nutrition has been suggested …”
Section: Discussionmentioning
confidence: 99%
“…A sub‐set of the NK data from study 1 is reported elsewhere . For study 2, data were collected using the A‐NSKQ; all the NK data from study 2 are reported elsewhere . The questionnaires were self‐administered online, making supervision impossible.…”
Section: Methodsmentioning
confidence: 99%
“…8 For study 2, data were collected using the A-NSKQ; all the NK data from study 2 are reported elsewhere. 7 The questionnaires were self-administered online, making supervision impossible. However, participants were instructed to answer questions honestly and not to look up answers to questions.…”
Section: Methodsmentioning
confidence: 99%
“…Databases were exported and IBM-SPSS version 21 was used to process the data. Scores for questions were calculated in two ways [17]:…”
Section: Data Management and Data Analysismentioning
confidence: 99%